The impact of country image and patient cosmopolitanism on medical tourism. Issue 1 (2nd January 2023) - Thelen, Shawn T.; Yoo, Boonghee
Abstract: The purpose of this research is to examine the impact affective/cognitive country image, cosmopolitanism, and satisfaction with insurance have on patient willingness to go abroad for surgery. Patients are presented a scenario where they select having knee replacement surgery domestically, having to pay all co-pays and deductibles, or abroad (Mexico, India, Israel) for free surgery at a JCI certified hospital. Results indicate cosmopolitanism impacts patient perception of medical tourism whilst affective and cognitive country image exhibit varying levels of significance. This study contributes to the literature by assessing factors that impact patient likelihood to travel abroad for surgery.